2008
DOI: 10.4049/jimmunol.180.12.7793
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Development of a Pancreatic Exocrine Disease in CD28-Deficient NOD Mice

Abstract: Autoimmune pancreatitis (AIP) is a heterogeneous autoimmune disease in humans characterized by a progressive lymphocytic and plasmacytic infiltrate in the exocrine pancreas. In this study, we report that regulatory T cell-deficient NOD.CD28KO mice spontaneously develop AIP that closely resembles the human disease. NOD mouse AIP was associated with severe periductal and parenchymal inflammation of the exocrine pancreas by CD4+ T cells, CD8+ T cells, and B cells. Spleen CD4+ T cells were found to be both necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 69 publications
4
26
0
1
Order By: Relevance
“…by immunization with self-antigens, injection of pathogens [35] or via adoptive transfer of autoreactive cells or T regs [36][37][38]. However, such models can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…by immunization with self-antigens, injection of pathogens [35] or via adoptive transfer of autoreactive cells or T regs [36][37][38]. However, such models can be highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in this model have shown that this mouse develops profound T1D as well as autoimmune exocrine disease due to limited Treg numbers (16,17). Given the more rapid course of FT1D in humans and the proposed role of viral infection in disease pathogenesis, we examined the effect of administration of a mimic of dsRNA, polyinosinic-polycytidylic acid [poly(I:C)], which has been suggested to increase pathogenic T cells and Tregs in conventional NOD mice (18), to CD28 2/2 NOD mice.…”
mentioning
confidence: 86%
“…Finally, antibodies anti-alfa-2-amylase have been recently described in a subgroup of patients affected by autoimmune pancreatitis presenting with fulminant diabetes [381], a form that is commonly considered 'non-autoimmune.' In these patients, the lymphocyte infiltrate affecting the exocrine component in autoimmune pancreatitis is extended to the islets [381] and may reveal shared immune-mediated mechanisms, as seem to be suggested in the NOD mouse [382].…”
Section: B Cells and Autoantibodiesmentioning
confidence: 99%